Effectiveness of SIMPEL Application (Reporting Information System) in Realized Acceleration of Village Administration Reporting in DPMD of Sidoarjo District: Efektivitas Aplikasi SIMPEL (Sistem Informasi Pelaporan) Dalam Mewujudkan Percepatan Laporan Administrasi Desa di DPMD Kabupaten Sidoarjo - Bernika Sucining Tyas; Tukiman (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2026)
The Sidoarjo Regency Government, as one of the innovative regions, has developed various public service applications, one of which is the SIMPEL Application (Reporting Information System) used to accelerate village administrative reporting. However, in its implementation, several issues remain, including low reporting compliance and disparities in application utilization among districts and villages. This study aims to describe and analyze the effectiveness of the SIMPEL Application in accelerating village administrative reporting at the Department of Community and Village Empowerment of Sidoarjo Regency. This research uses a qualitative descriptive approach. Data collection techniques include interviews, observations, and documentation. The analysis applies Duncan’s (1973) effectiveness theory, which consists of three indicators: goal attainment, integration, and adaptation. The results show that in terms of goal attainment, the SIMPEL Application has not been fully optimal, as indicated by the low level of village reporting that has not met the established deadlines. In terms of integration, socialization and technical guidance have been conducted by the department, but they have not been fully understood by all village officials, resulting in implementation challenges. Meanwhile, in terms of adaptation, there are still limitations in human resource capacity and readiness of village officials in transitioning from manual to digital reporting systems. In conclusion, the effectiveness of the SIMPEL Application in accelerating village administrative reporting in Sidoarjo Regency is not yet optimal. Improvements in human resource capacity, strengthening of socialization efforts, and increased commitment and discipline among village officials are necessary to enhance the effectiveness of the application.